Soil-structure interaction effect on seismic retrofit of a soft first-story structure. (August 2021) - Nasab, Mohammad Seddiq Eskandari; Chun, Seungho; Kim, Jinkoo
Abstract: This study investigates soil-structure interaction effects on seismic retrofit of soft first-story buildings. Analysis modeling methods of a soft first-story building, site effect, soil-structure interactions, and viscoelastic dampers (VEDs) are explained in detail. The seismic performance of the building is evaluated for different soil conditions using nonlinear dynamic analysis. According to the analysis results, the soil-structure system produces an increased seismic response and a higher demand for retrofit devices than a fixed base system, especially in site classes with low shear wave velocity. Fragility analysis shows that the probability of structural failure significantly increases when soil-structure interactions are considered, and that installation of VEDs significantly decreases the failure probability of the structure located on soft soil.